Psychological morbidity and its risk factors among migrant construction workers in Chengalpattu district – A cross-sectional study (International Journal of Occupational Safety and Health, 2025)
Introduction: Migrant construction workers, who form an essential workforce in the construction industry, face distinctive challenges such as job-related stress, workplace safety issues, financial instability, and difficulties arising from communication and cultural differences. Addressing psychological morbidity in this population is crucial not only to improve their quality of life. Hence, this study was conducted to assess the psychological factors such as anxiety, depression, and stress among migrant construction workers, as well as to evaluate the influence of social factors such as isolation, housing conditions, and cultural adaptation.Methods: This cross-sectional study was carried out among 350 migrant construction workers in the Chengalpattu district. A total of 4 construction sites were randomly chosen by lottery method and stratified random sampling was done in each construction site to obtain the required sample size. The Data was collected using a pretested semi-structured questionnaire and validated Depression, Anxiety, and Stress (DASS-21) Scale for assessing depression, anxiety, stress, and relevant data. Informed consent was obtained, and data were entered in MS Excel and analyzed by SPSS version 22.Results: Among the study participants, the prevalence of Depression, Anxiety, and Stress was found to be 44%, 32% and 38.6% respectively. Factors such as male gender, age ≤ 29 years, sleeping less than 6 hours per day, working more than 8 hours per day, lack of adequate housing facilities, and limited access to healthcare services were essential predictors for depression and stress. Working more than 8 hours per day was a necessary predictor of anxiety.Conclusion: Migrant construction workers are more prone for stress and other psychological health problems. Routine screening of both physical and mental health for workers should be carried out to ensure their well-being. Additionally, policies that address discrimination, improve living conditions, and enhance access to social services can contribute to a more equitable and fulfilling experience for migrant construction workers.